Plasma Pharmacokinetics and Tissue Distribution of Arctiin and Its Main Metabolite in Rats by HPLC-UV and LC-MS - He, Fan; Dou, De-Qiang; Sun, Yu; Zhu, Lin; Xiao, Hong-Bin; Kang, Ting-Guo (Planta Medica, 2012)
The pharmacokinetic profile of arctiin, the major active lignan in fruits of Arctium lappa L., was investigated. Its main meta“bolite arctigenin was identified by an LC-MS method, and an HPLC-UV technique was developed for the simultaneous quantification of the metabolite and arctiin in plasma and organs. Chromatographic separation was performed on an Agilent™ C18 HPLC column with acetonitrile and water by linear gradient elution. Arctiin and arctigenin were identified on-line by LC-MS. The pharmacokinetics and tissue distribution of arctiin and arctigenin were determined for the first time by using a simple, selective, and accurate HPLC method. The AUC0-t values of arctigenin were larger compared with arctiin after oral administration of arctiin. The concentration of the metabolite was significantly higher than the concentration of arctiin in the stomach and small intestine in rats after oral administration of arctiin, indicating that the stomach and small intestine were the major organs of arctiin metabolism. These findings could provide support for the clinical studies conducted with Fructus Arctii.
Keywords: arctiin; arctigenin; HPLC-MS; pharmacokinetics; tissue distribution; Arctium lappa; Compositae